1992
DOI: 10.1007/bf00317805
|View full text |Cite
|
Sign up to set email alerts
|

Wolf predation and snow cover as mortality factors in the ungulate community of the Bialowieża National Park, Poland

Abstract: Wolf-ungulate interactions were studied in the pristine deciduous and mixed forests of the Bialowieża National Park in 1985-1989. The study period included two severe and two mild winters. The community of ungulates inhabiting Bialowieża National Park consisted of red deer Cervus elaphus, 55% of all ungulates; wild boar Sus scrofa, 42%; and roe deer Capreolus capreolus, moose Alces alces, and European bison Bison bonasus, about 1% each. The average size of red deer groups increased from 2.7 (SD 2.35) in spring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
121
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(142 citation statements)
references
References 14 publications
16
121
1
4
Order By: Relevance
“…The estimated body-weight ratio of prey to wolf in this study was lower than that observed in other study areas (Jędrzejewski et al 2002) or for other coursing predators, such as the African wild dog (Lycaon pictus) in South Africa (Radloff and Du Toit 2004). Furthermore, the ratio was lower than expected according to the general prey to predator mass relationships reported by Jędrzejewski (1998), andCarbone et al (1999).…”
Section: Prey To Predator Body Mass Ratiocontrasting
confidence: 86%
See 3 more Smart Citations
“…The estimated body-weight ratio of prey to wolf in this study was lower than that observed in other study areas (Jędrzejewski et al 2002) or for other coursing predators, such as the African wild dog (Lycaon pictus) in South Africa (Radloff and Du Toit 2004). Furthermore, the ratio was lower than expected according to the general prey to predator mass relationships reported by Jędrzejewski (1998), andCarbone et al (1999).…”
Section: Prey To Predator Body Mass Ratiocontrasting
confidence: 86%
“…Proportion in scats is expressed as relative number of prey. Significance, assessed by calculating the confidence intervals for p=0.01 and type of selection (positive sign, selection and negative sign, avoidance) were consistent throughout the period, except for roe deer juveniles and fallow deer adults in 1996 (α) Jędrzejewski et al 1992), we found that the percentage of wild boar in wolf diet was related to both the percentage of wild boar in the ungulate community (R 2 =0.515, n=13, p= 0.006) and the ratio between late-winter density of wild boar and red deer (R 2 =0.560, n=13, p=0.003). With respect to this picture, Casentinesi Forests represent an outlier, as wild boar use was double that expected by its abundance in the ungulate community.…”
Section: Prey Use and Dietary Responsementioning
confidence: 99%
See 2 more Smart Citations
“…In our study, the recovery of roe deer carcasses suggested that mortality was highest in late winter and early spring, which is the time of year when snow cover can hinder the animal's movements and its ability to find food, leaving it vulnerable to starvation (Mysterud et al, 1997) and predation (Jȩdrzejewska et al, 1992). In addition, red fox is a potential predator of roe deer fawns (Panzacchi et al, 2008) and roe deer mortality is a subject worthy of further study.…”
Section: Discussionmentioning
confidence: 67%